Becoming a person of influence how to positively impact the lives of others - Maxwell, John C (Thomas Nelson, 1997)
Whatever your vocation or aspiration, you can increase your impact on others by Becoming a Person of Influence. Learn simple, insightful ways to interact more positively with others, and watch your personal and organizational success go off the charts. Managers will see their employees respond with new enthusiasm. Parents will connect with their children on a deeper level. Coaches will see players blossom. Pastors will reach more people. Salespeople will break records. With influence, you can achieve success at home, at work, and in every other area of life. Authors John Maxwell and Jim Dornan have spent most of their lives raising up influencers. With humor, heart, and unique insight, they share what they've gleaned from decades of experience in both business and nonprofit arenas. Best of all, their insights are practical and easy to apply to everyday life. Whether your desire is to build a business, strengthen your children, or reach the world, you can achieve it by raising your level of influence in the lives of others.